USING TRANSLATION AS A TEACHING TECHNIQUE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the role of translation as an effective teaching technique in language classrooms. It argues that translation enhances communicative interaction and actively engages learners in a conscious learning process. The paper also highlights the evaluative function of translation in assessing students’ understanding of texts. The article concludes that when appropriately applied, translation serves as a valuable and dynamic instructional tool in second language acquisition.